Tingkat Ketahanan Pangan Rumah Tangga Petani Garam Di Kabupaten Sampang Dengan Pendekatan FCS Dan FIES - Yaqin, Ainul; Soedarto, Teguh; Hendrarini, Hamidah (Jurnal Pertanian Terpadu, 2025)
Salt farmers in coastal areas such as Sampang Regency are vulnerable to low food security due to dependence on the production season and limited access to food. This study aims to measure the level of household food security of salt farmers and analyze the socioeconomic factors that affect it. The study was conducted on 100 respondents of cultivating salt farmers in Pangarengan District, with a quantitative approach through two main indicators: Food Consumption Score (FCS) and Food Insecurity Experience Scale (FIES). Data analysis used ordinal regression to identify significant variables that affect food security. The results showed that based on FCS, 61% of households were in the borderline category and 39% acceptable, while based on FIES, 92% were classified as food secure, 6% moderately food insecure, and 2% severely food insecure. Factors that have a significant effect on FCS are education, age, income, and distance to clean water sources. Meanwhile, for FIES, education and age are the dominant factors. These findings emphasize the importance of education-based interventions and access to basic infrastructure to improve the food security of salt farmer households in a sustainable manner.